LEARNING EFFECTIVENESS THROUGH VIDEO PRESENTATIONS AND WHATSAPP GROUP (WAG) IN THE PANDEMIC TIME COVID-19 - Kadek Adi Wibawa; I Putu Ade Andre Payadnya (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
This study aims to determine the effectiveness of learning through video presentations and Whatsapp Group (WAG) on the topic of vector space during the Covid-19 pandemic. The learning system is carried out online using videos developed by researchers and shared via WAG. This research is action research conducted in two cycles with each cycle consisting of four meetings. The subjects of this research were 14-second semester students in the Mathematics Education Study Program Faculty of Teacher Training and Education, Universitas Mahasaraswati Denpasar who took Linear Algebra courses. The data collected in this study were the researcher's actions, the results of the evaluation, and student responses to the video presentation and WAG applied by the researcher. The results of this study indicate that the application of video presentations and WAG on the topic of vector space during the Covid-19 pandemic was classified as effective, because the average student score increased 12.9% and 1.3% respectively with the class average before the action 68, after the action in cycle I 76.79 and after the action in cycle II 77.79. Student responses regarding the application of video presentations and WAG were very positive. This learning strategy can be used as a solution during the Covid-19 pandemic, which requires students and lecturers to carry out the teaching and learning process from home.